Sex Structure of Macrobrachium Nipponense Populations in Some Water Bodies of Uzbekistan - Kim, S. I. (American Journal of Biology and Natural Sciences, 2024)
The size-sex structure of various populations of freshwater shrimp Macrobrachium nipponense from natural and artificial reservoirs of the republic was studied. The studies showed the presence of significant differences between the ratio of males and females, as well as their sizes. In conclusion, conclusions are made about which populations of Macrobrachium nipponense are more profitable to take producers from to form the broodstock.